Selected institutions of the Polish civil service in the years 1996-2009. A comparative approach - Springer, Beata (Journal of Public Governance, 2013)
The study analyzes the evolution of the civil service in the years 1996-2009. It is based on incorporated legal acts which refer to the creation of the civil service corps and its organization structures, i.e. the Civil Service Office, the Head of the Civil Service, the Civil Service Council, The National Staff Resources, General Director, the Public Service Council. What is more, the author studies recruitment rules, the organization of preparatory service, staff evaluation and executive posts in the civil service. The aim of the paper is to discuss legal regulations developed and passed by the parliament and the government. It includes empirical data showing whether the statutory provisions were implemented. Moreover, it shows how the confusion in the matter resulted in problems of the entire system. In conclusion, it shows the lack of imagination on the part of the legislator or their disregard for the extremely important element of public life which is the civil service corps.